Ethical issues in participatory arts methods for young people with adverse childhood experiences - Gabriela Pavarini; Lindsay M. Smith; Nicola Shaughnessy; Anna Mankee‐Williams; Josita Kavitha Thirumalai; Natalie Russell; Kamaldeep Bhui (Wiley, 2021)
Abstract Context Participatory arts‐based methods such as photovoice, drama and music have increasingly been used to engage young people who are exposed to psychosocial risks. These methods have the potential to empower youth and provide them with an accessible and welcoming environment to express and manage difficult feelings and experiences. These effects are, however, dependent on the way these methods are implemented and how potential ethical concerns are handled. Objective Using the current literature on arts‐based health research as a foundation, this paper examines ethical issues emerging from participatory arts methods with young people with traumatic experiences. Results We present a typology covering relevant issues such as power, accessibility, communication, trust and ownership, across the domains of partnership working, project entry, participation and dissemination. Drawing on our extensive clinical and research experiences, existing research and novel in‐practice examples, we offer guidance for ethical dilemmas that might arise at different phases of research. Conclusion Adequate anticipation and consideration of ethical issues, together with the involvement of young people, will help ensure that arts methods are implemented in research and practice with young people in a fair, meaningful and empowering way. Patient or Public Contribution The issues reviewed are largely based on the authors' experience conducting participatory research. Each of the projects referenced has its own systems for PPI including, variously, consultations with advisory groups, coproduction, youth ambassadors and mentor schemes. One of the coauthors, Josita Kavitha Thirumalai, is a young person trained in peer support and has provided extensive input across all stages.